Pelaksanaan Pemberkasan Arsip di Pusat Administrasi Universitas Indonesia: Studi Kasus Bidang Perencanaan, Keuangan, dan Fasilitas - Laila, Nur; Mirmani, Anon (UI Scholars Hub, 2020)
Filing is a records processing activity by grouping documents into files in the work unit. Division Unit 2 at the Administrative Center of the Universitas Indonesia consists of 9 work units that create and capture record in accordance with their main tasks and functions, which are supporting core activities of the Administrative Center of the Universitas Indonesia. The records processing is based on the Universitas Indonesia's records classification scheme instrument. The research question is: how is the implementation of records filing in Division unit 2? Is the implementation in line with the instrument? The research purpose is to provide an overview of the records filing implementation in work units within Division Unit 2. I use qualitative research approaches with data collection techniques, interviews, participatory observation, and documentary analysis. The results show that, within Division Unit 2, four out of nine work units have carried out records filing according to the classification scheme and all work units have made a record inventory but have not included the location code for records storage.